Systematic review of photobiomodulation for multiple sclerosis - Oliveira de Andrade Filho, Vander; Amarante, Marina Oliveira Coura; Gonzalez-Lima, Francisco; Gomes da Silva, Sérgio; Cardoso, Fabrízio dos Santos (Frontiers in Neurology, 2024)
Background: Multiple sclerosis (MS) is an inflammatory chronic autoimmune and neurodegenerative disorder of the brain and spinal cord, resulting in loss of motor, sensorial, and cognitive function. Among the non-pharmacological interventions for several brain conditions, photobiomodulation (PBM) has gained attention in medical society for its neuroprotective effects. We systematically reviewed the effects of PBM on MS. Methods: We conducted a systematic search on the bibliographic databases (PubMed and ScienceDirect) with the keywords based on MeSH terms: PBM, lowlevel laser therapy, multiple sclerosis, autoimmune encephalomyelitis, demyelination, and progressive multiple sclerosis. Data search was limited from 2012 to July 2020. We followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The initial systematic search identified 126 articles. Of these, 68 articles were removed by duplicity and 50 by screening. Thus, 8 studies satisfied the inclusion criteria. Results: The reviewed studies showed that PBM modulates brain markers linked to inflammation, oxidative stress, and apoptosis. Improvements in motor, sensorial, and cognitive functions in MS patients were also observed after PBM therapy. No study reported adverse effects of PBM. Conclusion:These findings suggest the potential of PBM as a promising non-pharmacological intervention for the management of MS, although further research is needed to standardize PBM protocols and assess its long-term effects.